Piece of CAKE: A Comprehensive Queue Management Solution for Home Gateways - Høiland-Jørgensen, Toke; Täht, Dave; Morton, Jonathan (Karlstad University, 2018)
This is the evaluation dataset and online appendix for the paper "Piece of CAKE: A Comprehensive Queue Management Solution for Home Gateways".

Also published at https://www.cs.kau.se/tohojo/cake/
Keywords: Computer Sciences; Datavetenskap (datalogi)